Relationship between handgrip strength and timed up-and-go test on hospitalization costs in older adults: a population-based study - Kevin Yiqiang Chua; Kelvin Bryan Tan; Rachel Tong; Jon Barrenetxea; Woon-Puay Koh; Cynthia Chen (BMC Public Health)
Abstract Background Weak handgrip strength and slow timed up-and-go (TUG) time are known risk factors for hospitalization among older adults; however, few studies have investigated the relationships between these physical tests and future hospitalization costs. Methods We used data from 13,613 participants in the population-based Singapore Chinese Health Study who underwent assessment for handgrip strength and TUG time at a mean age of 74 years. Hospitalization costs for the subsequent year, among those who survived for at least one year thereafter, were ascertained via linkage with administrative healthcare finance data. We analyzed costs using a two-part model that contained a probit regression model in the first part, and a generalized linear regression model with gamma distribution and log link in the second. Results Handgrip strength showed a dose-dependent inverse relationship with hospitalization costs (P trend<0.001). Compared to the strongest quartile, participants in the weakest quartile experienced a 38.2% (95% CI: 18.0-58.5%) increase of US$599 (US$281-US$917) in mean costs. Conversely, TUG time demonstrated a dose-dependent positive association with hospitalization costs (P trend<0.001). Compared to the fastest quartile, participants in the slowest quartile had a 103.0% (72.1-133.9%) increase of US$1431 (US$1002-US$1859) in mean costs. We then examined combinations of handgrip strength and TUG time. Compared to participants who were both strong and fast, participants who were either weak or slow only had 12.9–48.7% higher mean costs. Meanwhile, participants who were both weak and slow experienced a 99.9% (68.5-131.4%) increase of US$1630 (US$1116-US$2144) in mean costs. Conclusions Weak handgrip strength and slow TUG time were independently associated with increased hospitalization costs among older adults.